Analisa Pilihan Ekonomi dalam Multisolusi Optimum Model "Linear Programming" - Yusmichad Yusdja (Jurnal Agro Ekonomi, 1994)
The first consideration of multisolution is laid on an idea that economics is a science subjected to a set of decision alternatives. Existing math models utilized, however, are generally static in nature reflected by only one solution as a result and there are no other alternatives provided. The unique solution gives no possibilities to develop economic decisions. Therefore, a multisolution calculation based on existing economic math models is required to be engineered. The main objective of this paper is to perform optimum multisolution of a Linear Programming Model. The conclusion of this paper show that the multisolution analysis on solution of LP's optimum condition finds several important issues. One of these conclusions shows that the LP's optimum solution is not always economically efficient. Besides the alternative owns similar objectives only different in how resource is allocated so that in the optimum alternatives there are possibility to insert the reality problem of resource into the decision making process.